La réforme de la PAC et les accords de l'OMC sur l'agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
S'adressant au Congrès des USA le 5 février 2003,...